Análise do sistema agroindustrial da soja e seus efeitos sobre o desenvolvimento econômico e social do Maranhão - Dörner, Stefan Hubertus (2017)
This thesis purposed an analysis of the economic, sociocultural and political-administrative dimensions of the agri-industrial soybean system and its effects on economic and social development in Maranhão. The project prioritized a systems approach and applied quantitative and qualitative methods, such as ICn, bibliographic research, direct observation, questionnaire and interviews. Data collection occurred during 2015/16 crop, suppliers, soybean producers and tradings provided primary data and official databasis such as RAIS, IBGE, National Treasury, Secretary of Maranhão state and TEGRAM export terminal and legislation secundary data. Economically, the agri-industrial soybean system generated important economic results, including 11.747 direct jobs, R$ 52 million in state taxes and U$ 700 million in exports. With reference to the sociocultural dimension, the effects are as well considerable, such as the establishment of an extensive network of social relations, caracterized by strong ties of cooperation and trust between agents, 672 entrepreneurs, 64 social organizations and several other forms of collaboration within the system, boosting competitiveness and innovation. The political-administrative dimension, even though nearly totally regulated by strict online control of its agents, should be seen with extreme concern due to the lack of support and cooperation by authorities. It is indispensable major involvement, professionalism and support by public administration to aggregate value on primary production and enable larger effects on socioeconomic development. Historically, the development of Maranhão illustrated that the priorization of agricultural primary exports and the inertia of the government in promoting value-aggregated production are condemned to failure. Thus, it should be followed the example of West Paraná, which iniciated soybean production in the 1960s and today has been consolidated as a very dynamic agri-industrial region and generated extense effects on socioeconomic development.